Arthropod biodiversity in European crops: Representative taxa for pest control and pollination - Grzegorz Sowa; Steven T.J. Droge; José Paulo Sousa; Lorraine Maltby (Ecological Indicators)
Arthropod biodiversity is critical for sustaining essential ecosystem services such as pest control and pollination, which underpin agricultural productivity. In Europe, agricultural intensification has led to significant changes in land use, contributing to the decline of terrestrial arthropods. This study quantifies the contributions of above‐ground, non‐target arthropods to these services across nine major European crops, six annual and three perennial, spanning 27 EU member states and a range of climatic and landscape conditions. Our analysis revealed that pest control assemblages (i.e. predators and parasitoids) were primarily composed of Coleoptera, Araneae, Diptera, and Hymenoptera, whereas pollination was mainly supported by Lepidoptera, Hymenoptera, and Diptera. Perennial crops generally harboured greater arthropod diversity, reflecting the benefits of more stable and structurally complex habitats. In contrast, specific pest control taxa, including ladybirds (Coccinellidae) and hoverflies (Syrphidae), were more abundant in annual crop systems, highlighting dynamic pest–prey interactions. Geographical variations in arthropod assemblages underscore the influence of climatic conditions and landscape features, suggesting that pest control assemblages are more region-specific, while pollinator assemblages exhibit less variation across zones. Key indicator taxa including families Braconidae, Ichneumonidae and Syrphidae, as well as genera Erigone and Coccinella were identified, for their ecosystem service roles across crops and zones providing robust metrics for environmental risk assessments and management of plant protection products. These findings support the integration of biodiversity monitoring with adaptive management strategies, offering a novel methodological framework for the development of ecological indicators that can inform sustainable agricultural practices and regulatory policies in European agroecosystems.